Effect of elevated temperature and cooling process on the tensile strength of rock - Zhu, Liying (2014)
Rock is a widely existing structural material. In severe situations such as fire disasters, the mechanical properties of rocks would be greatly affected, which threaten the stability of the whole structure. On the other hand the subsequent cooling process after heating also contributes to the risks of The tensile strength of rocks is much lower than the compressive strength thus the limiting property of rock is the tensile strength. This project aims to determine effect of elevated temperature and cooling process on the tensile strength of rock.